The effect of ginger use in chicken meatball production on lipid oxidation, sensory properties and other quality criteria - Hazar Suncak, Fatma Yağmur (International Society of Academicians, 2025)
In this study, ginger was used in different proportions (control, 0.25%, 0.50%, 0.75% and 1%) in the production of chicken meatball and the samples were cooked at different temperatures (175 ℃ and 200 ℃). Total aerobic mesophilic bacteria (TAMB) count, pH, moisture, thiobarbituric acid reactive substances (TBARS), ash, cooking yield and sensory analyses were applied on the samples. Ginger ratio (GR) in the meatballs caused statistically significant differences in TAMB, moisture, TBARS, ash, cooking yield and taste values (P<0.01). On the other hand, pH value was affected by this ratio at the level of P<0.01. Especially, with the increase in ginger ratio, lipid oxidation decreased while cooking yield increased. Cooking temperature (CT) caused changes in TAMB, TBARS and ash values. High cooking temperature caused a decrease in TAMB count and TBARS values. GR-CT interaction was statistically effective on TAMB, moisture, ash, cooking efficiency and general acceptability from sensory parameters. Considering the sensory analysis results, it was concluded that up to 0.75% ginger could be used in meatballs to increase functional properties and provide antioxidant and antimicrobial effects.
Keywords: Et Teknolojisi; Meatball; ginger; lipid oxidation; antioxidant; antimicrobial; Meat Technology